Exploration of the Dual Role of Dectin-1 in Tumor Development and Its Therapeutic Potential - Yuxuan Cai; Ke Wu (Current Oncology)
Immunotherapy, particularly immune checkpoint inhibitors like PD-1, PD-L1, and CTLA-4, has revolutionized cancer treatment. However, the role of the innate immune system, especially pattern recognition receptors, in cancer development and immunity is gaining more and more attention. Dectin-1, a C-type lectin receptor primarily involved in antifungal immunity, has emerged as a significant player in cancer biology, exhibiting both pro-tumor and anti-tumor roles. This dual function largely depends on the tumor type and microenvironment. Dectin-1 can promote immune responses against tumors like melanoma and breast cancer by enhancing both innate and adaptive immunity. However, in tumors like pancreatic ductal adenocarcinoma and colorectal cancer, Dectin-1 activation suppresses T cell immunity, facilitating tumor progression. This review explores the complex mechanisms by which Dectin-1 modulates the tumor microenvironment and discusses its potential as a therapeutic target for cancer treatment.